Overweight and obesity in school children aged 5 to 11 years participating in food assistance programs in Mexico Sobrepeso y obesidad en niños de 5 a 11 años de edad beneficiarios de programas de ayuda alimentaria en México - Lucía Cuevas-Nasu; Bernardo Hernández-Prado; Teresa Shamah-Levy; Eric A Monterrubio; María del Carmen Morales-Ruan; Lidia B Moreno-Macías (Instituto Nacional de Salud Pública, 2009)
OBJECTIVE: To determine the association between overweight and obesity among Mexican school-aged children and participation in the Liconsa milk and the School Breakfast food assistance programs. MATERIAL AND METHODS: Data from 15 003 school-aged children included in the Mexican National Health and Nutrition Survey 2006 (ENSANUT 2006) were analyzed. Information on body mass index (BMI) and participation in food assistance programs was obtained. Descriptive analyses were conducted and logistic regression models were adjusted. RESULTS: Prevalence of overweight and obesity was 17.3% and 9%, respectively. No significant association between overweight and obesity and participation in Liconsa was found. Among school-aged children in the middle socioeconomic status quintile, those enrolled in the School Breakfast program were more likely to be overweight than those not enrolled (OR= 1.6, 95% CI 1.1, 2.3). CONCLUSIONS: We found no association between the Liconsa and the School Breakfast programs and overweight or obesity in school-aged children. OBJETIVO: Determinar la asociación entre el sobrepeso y la obesidad en niños de edad escolar y la pertenencia a los programas de asistencia alimentaria Liconsa o Desayunos Escolares en México. MATERIAL Y MÉTODOS: Se analizó la información de 15 003 niños en edad escolar de la Encuesta Nacional de Salud y Nutrición 2006 (ENSANUT 2006). Se obtuvo el índice de masa corporal (IMC) e información sobre participación en programas de asistencia alimentaria. Se realizaron análisis descriptivos y se ajustaron modelos de regresión logística. RESULTADOS: La prevalencia de sobrepeso y obesidad fue de 17.3 y 9%, respectivamente. No hubo asociación significativa entre el sobrepeso y obesidad y ser beneficiario de Liconsa. En el quintil socioeconómico medio, los beneficiarios de Desayunos Escolares tuvieron mayores posibilidades de presentar sobrepeso que los no beneficiarios (RM= 1.6, IC 95% 1.1,2.3). CONCLUSIONES: No se encontró asociación entre ser beneficiario de Liconsa o Desayunos Escolares con el sobrepeso y obesidad en este grupo de edad.